Tang shi li de Zhongguo : wang chao jian ying - Hulijia (Chengdu : Sichuan Juvenile and Children's Publishing House, 2022)
"China in Tang Poetry" is a picture book that skillfully combines literature and history with Tang poetry. This book is one of the "Dynasty Silhouettes", based on more than 100 Tang poems, refining the "history lessons" in the poems, from the rise and fall of the dynasty to the lives of the people, through several themes, so that children can have a more comprehensive and in-depth understanding of the Tang Dynasty in the poems, so as to truly understand the poems of the Tang Dynasty and experience the beauty of Tang poetry.
In simplified Chinese script
Keywords: Children's poetry, Chinese; Chinese poetry -- History -- Tang dynasty, 618-907; China, -- History -- Tang dynasty, 618-907